Analysis of the Correlation of Microstructure, Instrumental Texture, and Consumer Acceptance of Shortbread Biscuits with Selected Sweeteners and Fibre - Agata Marzec; Alicja Stępień; Agnieszka Goclik; Hanna Kowalska; Jolanta Kowalska; Agnieszka Salamon (Applied Sciences)
Biscuits are characterized by their popular sweet taste, but they have a poor nutritional profile due to their high sugar and saturated fat content, along with low fibre levels. Their sweetness primarily comes from sucrose, which not only determines the flavour but also performs several technological functions, making it difficult to replace in pastry products. Commercial sweeteners and soluble fibres designed for pastry products are available. Therefore, it is necessary to test the feasibility of using these ingredients in biscuit formulations and assess their impact on biscuit quality. Concurrently, the correlation analysis of dough rheological parameters, structure, and instrumental texture parameters with sensory characteristics will help identify which parameters are strongly correlated and can be used to predict biscuit quality. The purpose of this study was to investigate the dough rheological properties, structure, texture, and sensory characteristics of biscuits in which sucrose was replaced by the commercial sweeteners Tagatesse, maltitol, and erythritol–stevia, with the addition of soluble fibres Nutriose® FB (wheat fibre) and PromOat 35 (oat fibre). At the same time, a correlation analysis was conducted between dough rheological parameters (stickiness, work of adhesion, dough strength) and biscuit quality parameters, such as water activity, water content, colour, texture (pore area, pore shape, pore elongation), and instrumental texture properties (hardness, brittleness, number of acoustic emission (AE) events, AE event energy), with sensory discrimination evaluated through a consumer test. The use of wheat and oat fibres in combination with sucrose resulted in biscuits with lower apparent density, increased porosity, and weaker texture (fracturability, hardness, number of AE events), yet they had better sensory properties compared to biscuits containing sucrose alone. Replacing sucrose with sweeteners combined with fibres led to a deterioration in the sensory quality of the biscuits and a significant change in the dough’s rheological properties. Regardless of the type of sweetener, biscuits with wheat fibre were rated better than those with oat fibre. Of the tested sweeteners, only maltitol combined with wheat fibre resulted in a sensory quality similar to that of sucrose biscuits. Correlation analysis of all measured biscuit quality parameters showed that only the number of AE events had a strong positive correlation with all tested sensory attributes. Porosity was only correlated with sensory crispness, and fracturability was correlated with sweetness, taste, and overall acceptability. Therefore, it appears that the number of AE events recorded at the time of breaking may be a reliable parameter for predicting biscuit quality.